Returns to Capital in Microenterprises: Evidence from a Field Experiment - de Mel, Suresh; McKenzie, David; Woodruff, Christopher (2012)
We use randomized grants to generate shocks to capital stock for a set of Sri Lankan microenterprises. We find the average real return to capital in these enterprises is 4.6%-5.3% per year), substantially higher than market interest rates. We then examine the heterogeneity of treatment effects. Returns are found to vary with entrepreneurial ability and with household wealth, but not to vary with measures of risk aversion or uncertainty. Treatment impacts are also significantly larger for enterprises owned by males; indeed, we find no positive return in enterprises owned by females.